Wokół „Patologii transformacji” Witolda Kieżuna - uwagi krytyczne - Zieliński, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In the first half of the 1970s Witold Kieżun, basing on the contributions of the Polish school of praxiology, presented his theory of pathology of organization. Recently in the book on pathology of transformation he attempted — in my view, unsuccessfully — to apply this theory to the analysis and evaluation of the process of systemic and especially economic transformation in Poland. In this paper I try to present a partial critique of his position. First, the theory of pathology organization, that is reconstructed in the first chapter of his last book, is largely incompatible with market conditions and as such it impedes the understanding of the working of organizations within the framework of market calculative environment — because of it I point to some defects of the said theory. Second, this theory has little in common with later description of pathology of transformation, that is based not on the theory of praxeology, but on the ideology of neocolonialism — therefore I present also a critique of basic propositions of this ideology. Third, I indicate, basing on some case studies, that Kieżun’s selection of data in the description of privatization processes is largely biased — considering the wider context allows us to understand that the scale of “pathologies” during privatization had to be much smaller than is suggested in the book. Fourth, I point out that vague alternative presented by Kieżun does not take into account the realities of transformation, although — as is implied in many passages of the book — he was well aware of them
Keywords: transformation; praxiology; pathology; neocolonialism; privatization; asset pricing